Firms and public service provision in Russia - Pertti Haaparanta; Tuuli Juurikkala; Olga Lazareva; Jukka Pirttilä; Laura Solanko; Ekaterina Zhuravskaya (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This paper reports first results from a survey of 404 middle-sized and large manufacturing firms from 40 Russian regions in April-June 2003.We examine the extent of social service and infrastructure provision by the firms and the firms assessment of the quality of public infrastructure and the regulatory environment.Background information of ownership, investment, performance, competition, and finance decisions of the firms is also gathered. The data reveal that despite major divestments of social services during 1990s, a great majority of firms still provide at least some form of social services.For example, 56% of the firms have their own housing or support local housing, and 73% of the firms have recreation facilities or support employee s recreation activities. While managers view the social service provision as non-essential and costly, many of the firms continue to provide these services, even to users other than their own workforce. The quality of public infrastructure is generally assessed as being good or satisfactory; the respondents were the least satisfied with the quality of roads.Over a half of the firms provide their own heat, but mainly due to technological reasons although public service interruptions do occur and 24% of the firms give support to the maintenance and construction of public road network. The regulatory burden the firms face continues to be severe.In more than half of the firms, for example, the general manager has to spend more than two weeks in negotiations about public infrastructure with the authorities. These descriptive results indicate that there is still a lot scope for improvement in the quality and quantity of public service provision in Russia.Enterprises are still engaged rather heavily in social service provision, road network would require improvements, and the easing of regulatory burden should continue. Addressing these questions is likely to be vital for the sustainability of investments and growth in Russia. The paper is part of the project Infrastructure and Welfare Services in Russia: Enterprises as Beneficiaries and Service Providers financed by the Academy of Finland (project number 200936), the World Bank, and Yrjö Jahnsson Foundation.The project has also received support from the Bank of Finland Institute for Economies in Transition.
URN:NBN:fi:bof-201408072052
Keywords: 330